An Asymptomatic Mandibular Radiolucency: First Sign of Follicular Thyroid Carcinoma - Lakshmi S. Garladinne; Steven B. Whitaker; Jerry E. Bouquot (Taylor & Francis Group, 2024)
Background Metastatic carcinomas to the jaws are a rare occurrence. Most notable primary sources within the literature are breast, lung and kidney, followed by GI, prostate and thyroid. In almost all instances, there is a primary site already identified, but very occasionally the metastases are the first sign of a problem. Notable other, less obvious, clinical expressions of malignancy are weight loss, loss of appetite, fever and chills.  Again, these can present with no obvious site of a primary cancer. A unique feature of our case is the lack of primary symptoms.Case Description The patient initially presented for teeth extraction a year previously, followed by a slow but eventually large expansion of the left mandibular ramus. The underlying radiolucency gave no apparent signs or symptoms suggestive of malignancy. Incisional biopsy showed a glandular neoplastic proliferation with apparent thyroid follicles noted at the margins. Special imaging and immunostains confirmed a tissue origin in the thyroid gland. The patient was referred to Otolaryngology for definitive treatment. The jaw lesion was treated by radical surgical excision and the neck site was treated, after microscopic confirmation of a follicular thyroid carcinoma, via total thyroidectomy.Practical Implications This case illustrates the importance of interdisciplinary treatment and how it can lead to an optimal outcome for the patient's prognosis.